Imagining and emplacing net zero industrial clusters: A critical analysis of stakeholder discourses - Huei‐Ling Lai; Patrick Devine‐Wright (Geo: Geography and Environment, 2024)
Abstract Decarbonizing industrial sectors is a critical global challenge, involving the creation of new industrial spaces—‘net zero industrial clusters’—co‐locating energy sectors and ‘hard‐to‐abate’ industries such as oil refining and steelmaking. This paper provides the first empirically grounded geographical investigation of these emerging spaces. It employs a place‐based research agenda to unpack how UK net zero industrial clusters (ICs) are imagined and emplaced in policy and industry discourses through place‐based naming, spatial configuring and mapping activities. By conducting document analysis, 33 in‐depth stakeholder interviews and five field trips to three UK case studies, we show how cluster imaginaries vary across cases and policy contexts in terms of constituents, focus and purpose. Ontological complexity is compounded by different rationales among stakeholders in configuring clusters and by contested cluster naming and boundary setting. This ambiguous, evolving spatiality raises important political and justice concerns over who and where is excluded in cluster building. These findings advance the geographies of low‐carbon transitions by showing: (1) ways that ICs' spatial embeddedness, which underlies cluster spatial configurations, helps increase industry actors' recognition of their economic, social and cultural ties with the places of their making, even if this risks path dependency; (2) how fluid cluster boundaries, reflected in cluster names and maps, emphasize the value of a network topology of scale to enable spatially inclusive, multi‐scalar climate mitigation. Finally, we argue that a place‐sensitive net zero policy mindset is vital for fulfilling ICs and the UK's decarbonization potential in a manner that is both fair and locally grounded.